The percentage of Bean Common Mosaic Virus (BCMV) carried by seeds and detection of virus position inside long beans (Vigna sinensis L.) seeds in Bali - NI LUH PUTU CITRA INNOSENSIA; I GEDE RAI MAYA TEMAJA; I DEWA NYOMAN NYANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
The percentage of Bean Common Mosaic Virus (BCMV) carried by seeds and detection of virus position inside long beans (Vigna sinensis L.) seeds in Bali Long bean (Vigna sinensis L.) is a horticulture crop with an essential economic value in Indonesia and Bali. Long beans productivity in Bali reached 6023 tons in 2013, and decreased to 5157 tons in 2014. Cases of disease that lowers the production of long beans in Bali were caused by Bean Common Mosaic Virus (BCMV) infection by 56.06%. BCMV can be brought by the seeds (seed-borne disease) and can infect long beans plants since the early stage of development. This research aims to evaluate the percentage of BCMV transmission by commercial long beans seeds, commonly used by farmers in Bali, and observe the location of BCMV inside the seeds. The morphological observation was used to evaluate the percentage of BCMV brought by the seeds by observing BCMV specific symptoms appear on two weeks old long beans seedlings. To observe the location of BCMV inside the long bean seeds, harvested seeds from an infected plant were separated to collect the cotyledon and embryo. The RT-PCR technique was used as a method in this research. The result showed the percentage of BCMV brought by long beans seeds used by farmers in Bali categorized as high. The percentage of BCMV brought by seeds from the highest to the lowest were; variety A 48.39%, variety B 46.66%, variety C 43.59%, variety D 37.83%, variety E 22.86%, and variety F 22.72%. The variation of the symptoms was mosaic vein banding, malformation, and dwarf plant with wrinkled leaves. The BCMV brought by long bean seeds was resides on the embryo.